2020
DOI: 10.3791/61252
|View full text |Cite
|
Sign up to set email alerts
|

A <em>Drosophila</em> Model to Study Wound-induced Polyploidization

Abstract: Polyploidy is a frequent phenomenon whose impact on organismal health and disease is still poorly understood. A cell is defined as polyploid if it contains more than the diploid copy of its chromosomes, which is a result of endoreplication or cell fusion. In tissue repair, wound-induced polyploidization (WIP) has been found to be a conserved healing strategy from fruit flies to vertebrates. WIP has several advantages over cell proliferation, including resistance to oncogenic growth and genotoxic stress. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…S1A " type="url"/> – ). We assayed for endocycle entry using the thymidine analog EdU as an S phase marker, as cells undergo successive S phases with each endocycle during WIP ( Bailey et al, 2020 ; Losick et al, 2016 ). At 2 dpi, we observed 178 EdU + nuclei on average for the control around the wound site as previously reported, whereas mys knockdown reduced the mean number of EdU + epithelial nuclei to 74 ( mys RNAi#2 ) and 40 ( mys RNAi#3 ) ( …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1A " type="url"/> – ). We assayed for endocycle entry using the thymidine analog EdU as an S phase marker, as cells undergo successive S phases with each endocycle during WIP ( Bailey et al, 2020 ; Losick et al, 2016 ). At 2 dpi, we observed 178 EdU + nuclei on average for the control around the wound site as previously reported, whereas mys knockdown reduced the mean number of EdU + epithelial nuclei to 74 ( mys RNAi#2 ) and 40 ( mys RNAi#3 ) ( …”
Section: Resultsmentioning
confidence: 99%
“…To confirm that epithelial ploidy was reduced, we directly measured nuclear ploidy in uninjured (−) and 3 dpi (+) epithelia. Our previous studies have shown that the uninjured epithelial nuclei are diploid (2C) and therefore can be used as an internal control to measure changes in the fly epithelial cell ploidy ( Bailey et al, 2020 ; Losick et al, 2013 ). As expected at 3 dpi, we observed that 41% of epithelial nuclei were polyploid compared to only 4% in uninjured control epithelial cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epithelial ploidy was calculated according to (Bailey et al, 2020). Samples from 5d and 40d old flies were dissected and stained as described above, then imaged with the same exposure time.…”
Section: Drosophila Imaging and Analysismentioning
confidence: 99%